Endothelial Progenitor Cell-Based Therapy for Pulmonary Arterial Hypertension. Issue 8 (August 2013) - Yang, Jin-Xiu; Pan, Yan-Yun; Zhao, You-Yang; Wang, Xing-Xiang
A growing body of evidence in animal models and clinical studies supports the concept that endothelial progenitor cell (EPC)-mediated therapy ameliorates pulmonary arterial hypertension (PAH) and thus may represent a novel approach to treat it. Conversely, several experimental findings suggest that EPCs may be involved in PAH pathogenesis and disease progression. These discrepant results confuse the application of EPC transplantation as an effective treatment strategy for PAH. To improve the study of EPC transplantation in PAH therapy, it is high time that we resolve this dilemma. In this review, we examine the pathobiological changes of PAH, the characteristics of EPCs, and the underlying mechanisms of EPC effects on PAH.